FxLMS versus H∞ Control for Broadband Acoustic Noise Attenuation in a Cavity. Issue 1 (July 2017) - Boultifat, Chaouki; Loiseau, Paul; Chevrel, Philippe; Lohéac, Jérôme; Yagoubi, Mohamed
Abstract: This paper deals with active noise control (ANC) in an enclosure on a broadband frequency range. It aims to compare two control strategies: (i) an adaptive control approach namely FxLMS control, (ii) a robust H ∞ control, in the SISO (single input single output) case. Only feedback scheme is considered and disturbance sources are assumed to be unknown. For the aim of a fair comparison focusing on the same frequency range of attenuation, a new FxLMS algorithm with a weighting filter is proposed. Finally, achievable performances of each control are analyzed through simulation and experimental results driven on an instrumented setup.